2022
DOI: 10.1021/acsabm.2c00123
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanomaterial-Based Platforms to Combat COVID-19: Diagnostics, Preventions, Therapeutics, and Vaccine Developments

Abstract: The COVID-19 pandemic caused by the SARS-CoV-2, a ribonucleic acid (RNA) virus that emerged less than two years ago but has caused nearly 6.1 million deaths to date. Recently developed variants of the SARS-CoV-2 virus have been shown to be more potent and expanded at a faster rate. Until now, there is no specific and effective treatment for SARS-CoV-2 in terms of reliable and sustainable recovery. Precaution, prevention, and vaccinations are the only ways to keep the pandemic situation under control. Medical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 248 publications
(398 reference statements)
0
24
0
Order By: Relevance
“…SARS-CoV-2 is a single-stranded positive RNA virus. Spike (S), nucleocapsid (Nuc), envelope (E), and matrix (M) are four important structural proteins of coronavirus. , Severe acute respiratory syndrome virus (SARS-CoV) and Middle East respiratory syndrome virus (MERS-CoV) have caused major epidemics during the last two decades. The novel virus was named SARS-CoV-2 due to its genomic similarity with SARS-CoV, MERS-CoV, and bat coronavirus RaTG13 .…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is a single-stranded positive RNA virus. Spike (S), nucleocapsid (Nuc), envelope (E), and matrix (M) are four important structural proteins of coronavirus. , Severe acute respiratory syndrome virus (SARS-CoV) and Middle East respiratory syndrome virus (MERS-CoV) have caused major epidemics during the last two decades. The novel virus was named SARS-CoV-2 due to its genomic similarity with SARS-CoV, MERS-CoV, and bat coronavirus RaTG13 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the binding between the receptor-binding domain (RBD) of the spike protein in SARS-CoV-2 and ACE2 peptide-attached plasmonic-magnetic heterostructures is the most important parameter to determine whether the newly designed heterostructures have the capability for blocking COVID-19 infections, we have determined binding affinity between different variants SARS-CoV-2 RBD and ACE2 peptide-attached heterostructures. For this purpose, we used the enzyme-linked immunosorbent (ELISA)-like assay using His-tag protein. For this purpose, different variants of SARS-CoV-2 RBD were adsorbed to a 96-well plate overnight at 4 °C. Experimental details are reported in Supporting Information. Figure B shows the binding curve between ACE2 peptide-attached plasmonic-magnetic heterostructures and the Alpha variant (B.1.1.7) spike protein-RBD.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the emergence of mutations on the spike (S) protein gene in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the death toll for the coronavirus disease-19 (COVID-19) pandemic reached more than 6.2 million as of June 2022. As per Centers for Disease Control and Prevention (CDC), due to the mutations in the spike gene, different SARS-CoV-2 lineages such as B.1.1.7 (Alpha variant), B.1.351 (Beta variant), B.1.1.28.1 (Gamma variant), B.1.617.2 (Delta variant), and B.1.1.529 (Omicron variant) have emerged. It is also reported that Omicron and Delta variants spread more easily than earlier variants. Recent clinical studies indicate that due to 15 mutations in the receptor-binding domain (RBD), the delta and omicron strains have the capability to escape the immune response, which has been acquired by people in our society via COVID-19 infection or through several vaccines which have been administered in last two years. All of the above data clearly indicate that designing a new bioconjugated material-based strategy to separate, detect, and block the omicron variant interactions are very important for our society. Driven by the need, here we report the development of magnetic-plasmonic heterostructures which synergistically exhibit magnetic and plasmonic characteristics for magnetic separation, plasmonic-based SERS identification, and prevention of the different variants virus to enter into the host cells via blocking spike the protein RBD binding with the host cells’ angiotensin converting enzyme 2 (ACE2).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their cost-effective advantages over conventional devices, such as their small size, light weight, low power consumption, flexibility to create them in batches, superior performance, and more precise findings, MEMS devices have become increasingly popular. These benefits have made BioMEMS-based devices' applications in the biological and biomedical domains particularly promising [20][21][22][23][24][25][26][27] . For particular uses a variety of BioMEMS-based devices have been created [28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%